VOCATIONAL EFL STUDENTS’ CHALLENGES IN ENGLISH ORAL PRESENTATION - Syam, Ferawaty; Umar, Nugrah Juniar; Faiqoh, Elok; Pratiwi, Widya Rizky; Hardianti, Hardianti (Institut Agama Islam Negeri (IAIN) Bone, 2024)
This study aims to explore the challenges faced by vocational EFL (English as A Foreign Language) students during English oral presentations in class. A total of 30 students were selected as the sample through purposive sampling technique. Data were collected based on observation, questionnaires, and semi-structured interviews. The results showed that the most significant challenge faced by the students in class was anxiety during the question and answer session in the presentation activity. Technical difficulties during presentations were also a recurring problem. In addition, students also considered speaking and pronunciation as the most difficult aspects of their presentations. The results of this study provide knowledge that can also be a reference in overcoming anxiety, technical obstacles, and efforts to improve students' English skills, especially in the aspect of speaking as the main provision in classroom presentations.